Flash vacuum pyrolysis of azolylacroleins and azolylbutadienes - Lucero, Paola Liliana (2012)
2-Aryl-5-acroleinyl-1,2,3,4-tetrazoles (1aed) and 2-aryl-5-butadienyl-1,2,3,4-tetrazoles (1eeg) weresubjected to flash vacuum pyrolysis. Acroleinyl derivatives resulted in nitrogen extrusion to give nitrilimines followed by ring closure to give the corresponding indazoles 3aed in good yields. On the other hand, butadiene derivatives underwent ring fragmentation to give p-substituted anilines without formation of the expected indazoles. Differences between thermal behaviour of 2-(4-chlorophenyl)-5-acroleinyl-1,2,3,4-tetrazole (1c) and 1-(4-chlorophenyl)-4-acroleinyl-1,2,3-triazole (2) were studied in details. DFT calculations have been used to examine the nitrilimine and carbene nature of the intermediates involved in the thermal reactions of azolyl derivatives.